Distal Femur Morphological Discrepancy Compared with Total Knee Arthroplasty Implants in Indonesia - Sentana, Okkie Mharga; Utomo, Pamudji (The Hip and Knee Journal, 2023)
The prosthesis of knee joint in total knee arthroplasty (TKA) can give better fixation and stabilization if it’s chosen properly. Most of prosthesis have been designed to be compatible with western population, not for Asian population. Whether the implant size need to be adjusted with ethnics and gender still being a controversy. Aim to define whether the morphology of Distal Femur, among men and women in Indonesia have discrepancy and to assess compatibility of the prosthesis size in Indonesia. This study was a descriptive cross-sectional study that conducted at Prof. Dr. R Soeharso’s Orthopaedic Hospital – Surakarta, Indonesia, using purposive quota sampling methods. The inclusion criteria MRI knee joint of men and women (age ≥ 18 years old) which have soft tissue injury of knee joint. The morphological measurement of Distal Femur with the use of certain Software. Then, the data were analyzed with SPSS ver.17 using independent T-Test. The results among 130 patients, we found that Women’s fML were narrower than men. While the ratio aspect of femur implants compared to gender, showed that it was not compatible for men, but more compatible for women. The conclusion there is discrepancy of morphological size of Distal Femur among men and women in Indonesia. It causes incompatibility of using TKA implant in men patients in Indonesia, which more suitable for women size.